Revenue Segmentation of Nepal Telecom - Parajuli, Dilip (PYC Nepal Journal of Management, 2010)
This paper is originally presented at the “International Seminar on Management” on “Enhancing Enterprise Effectiveness for Global Challenges” organised by Brihaspati College, Siddharthnagar on 3rd and 4th April 2010. The author acknowledges that the printed version of the paper has come after the suggestions from the Editorial Committee. The paper attempts to evaluate revenue segmentation of Nepal Telecom using factor analysis technique. The study finds that there are two principal components in income of Nepal Telecom as major and minor sources of income. The major income sources includes domestic trunk and telephone, local telephone, international telephone and others while the minor sources of income includes international telegraph, domestic telegraph, international telex, lease circuit and tele-fax. Similarly, the regression analysis reports a high degree of significant effect of major sources of income, on the contrary minor sources of income exerts insignificant effect on the revenue of Nepal Telecom.